2022
DOI: 10.3390/healthcare10061028
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Methylprednisolone Compared to Other Drugs for Pain, Swelling, and Trismus Control after Third Molar Surgery: A Meta-Analysis

Abstract: The purpose of this systematic review and meta-analysis was to assess the efficacy of methylprednisolone compared to other drugs to control postoperative complications following third molar surgery. PubMed and Google Scholar were used for article searching. Thereafter, the trials meeting the selection criteria and with high methodological quality, according to the Cochrane Collaboration’s risk of bias tool, were included in this study. The inverse variance test and mean difference using the Review Manager Soft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…However, another meta-analysis that evaluated the effectiveness of methylprednisolone against placebos in M3M surgery suggested that methylprednisolone significantly reduced pain, edema, and trismus in the early postoperative period [ 25 ]. Another meta-analysis evaluating the effectiveness of methylprednisolone against other anti-inflammatory drugs showed that methylprednisolone was significantly better in reducing trismus after 7 postoperative days [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, another meta-analysis that evaluated the effectiveness of methylprednisolone against placebos in M3M surgery suggested that methylprednisolone significantly reduced pain, edema, and trismus in the early postoperative period [ 25 ]. Another meta-analysis evaluating the effectiveness of methylprednisolone against other anti-inflammatory drugs showed that methylprednisolone was significantly better in reducing trismus after 7 postoperative days [ 26 ].…”
Section: Discussionmentioning
confidence: 99%